Teachers’ Attitudes Towards Diversity and Inclusive Education in Learning Communities (Revista Lusófona de Educação, 2025)
The paper presents a study carried out as part of the research project LC4Inclusion - On the road toschools as communities for inclusion. It focuses on teachers’ attitudes towards inclusive education and diversity in groups of schools involved in the Portuguese Network of Learning Communities INCLUD-ED, which theDirectorate-General for Education promoted at national level. 154 responses to a questionnaire, inspired by theIndex for Inclusion and previously validated in Portuguese schools, were analysed. The results are in line withother studies and point to an overall positive attitude towards the three dimensions analysed in the factor analysis: Diversity and educational inclusion; Inclusive cultures; Inclusive classroom practices, as well as positive andsignificant correlations between these dimensions, revealing their interdependence. The results also revealedthat attending training in inclusive education, self-perceived knowledge about diversity and inclusion, positiveprevious experiences with students with specific needs and the lower levels of education at which teachersteach are significantly associated to more positive attitudes towards inclusive education.Keywords: Teachers’ attitudes; Diversity; Inclusive cultures; Inclusive policies; Inclusive practices.